Reconstructing Amelia : a novel - McCreight, Kimberly (New York : Harper, 2013)
When her high-achieving fifteen-year-old daughter Amelia supposedly commits suicide after she is caught cheating, litigation lawyer and single mother Kate Baron, leveled by grief, must reconstruct the pieces of Amelia's life to find the truth and vindicate the memory of the daughter whose life she could not save.
Keywords: Single mothers -- Fiction; Daughters -- Death -- Fiction; Private schools -- Fiction; Single parents -- Fiction; Daughters -- Death -- Fiction; Private schools -- Fiction